2010
DOI: 10.1016/j.amjopharm.2010.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient medication reconciliation at admission and discharge: A retrospective cohort study of age and other risk factors for medication discrepancies

Abstract: Background Medication discrepancies are unintended differences between medication regimens (ie, between a patient’s home regimen and medications prescribed on admission to the hospital). Objective The goal of this study was to describe the incidence, drug classes, and probable importance of hospital admission medication discrepancies and discharge regimen differences, and to determine whether factors such as age and specific hospital services were associated with greater frequency of medication discrepancies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
105
7
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(138 citation statements)
references
References 25 publications
(24 reference statements)
19
105
7
3
Order By: Relevance
“…1,3,12,14,15,23,25 Several factors we found to be associated with medication reconciliation errors, such as older age and number of preadmission medications, were confirmed by others. 11,12,14,15 However, in one study fewer unintentional medication discrepancies were associated with age over 85 compared to age less than 50. 12 Herrero-Herrero et al found that the number of preadmission medications predicted unjustified discrepancies (i.e.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…1,3,12,14,15,23,25 Several factors we found to be associated with medication reconciliation errors, such as older age and number of preadmission medications, were confirmed by others. 11,12,14,15 However, in one study fewer unintentional medication discrepancies were associated with age over 85 compared to age less than 50. 12 Herrero-Herrero et al found that the number of preadmission medications predicted unjustified discrepancies (i.e.…”
Section: Discussionsupporting
confidence: 75%
“…We did not investigate medication errors from in-hospital transfers nor assess the clinical impact of medication errors, though the relationship between total errors, clinically relevant errors, and ADEs have been described in several prior studies. 3,4,11,12,14,15,22,23,34 Clinically relevant medication errors were classified at the discretion of the pharmacists, thereby introducing possible bias in the judgment of these outcomes. The potential of errors to cause harm was not formally adjudicated by a blinded panel of clinicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medication discrepancies frequently occur surrounding an acute hospitalization, both at admission and at discharge., [1][2][3] Medication discrepancies are differences between medication regimens (i.e. between medications prescribed on discharge from the hospital and a patient's home regimen).…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, apenas 44% foram alertados explicitamente sobre novos medicamentos prescritos ou alterações de doses, e 12% receberam instruções por escrito para parar de utilizar medicamentos que faziam uso antes da hospitalização e que foram suspensos (UNROE et al, 2010).…”
Section: Orientação Ao Paciente E/ou Cuidadorunclassified